An Allegorical Comparison of Garshaspnameh and Faramarznameh and Lady Gashsapnameh - Salimi, Hossein; Alavi, Bashir (LANGUAGE ART, 2022)
Undoubtedly, magic and sorcery have a history as old as human history. Fantasy and its process are topics that can be explored in the literature. Iranian epics also have such dimensions. Especially since they have a close relationship with myths, legends and epics. Mandatory components in fantasy texts are magic, sorcery and sorcery. This article is an attempt to pay attention to the similarities and differences between the use of this component in the Garshaspnameh system with Faramarznameh and Banogshspnameh. To achieve the result, an attempt has been made to first provide a brief definition of fantasy, and then to examine the characteristics of Gershasp and Faramarz and Banu Gosps in these systems. Finally, by mentioning the evidence, the frequency of use of magic and the reason for the superiority of Garshaspnameh in the fantasy dimensions of magic should be compared. In comparing the frequency of use of these elements, first there are Garshaspnameh letters, then Faramarznameh letter, and finally Lady Gashsapnameh letter. Among the reasons for this superiority in the Garshaspnameh are the existence of travel and its types and the poet's mentality, as well as his closeness to the Khorasani style compared to the other two poems.